Die rol van die see in die Patmos-visioene - J du Preez (Acta Theologica)
Older and newer commentaries on Revelation as well as other studies regarding this book, reveal virtually throughout a very negative view on the rol of the sea in John's visions. The author of this article examines all the relevant sections in Revelation and concludes that, although in John's final vision of the new world there seems to be no place for the sea (21:1), the sea nevertheless virtually throughout Revelation plays a more positive than negative role and is, therefore, unjustly viewed in such a negative light. The theological-ecological implication of this is indicated.